TRAIL pathway is associated with inhibition of colon cancer by protopanaxadiol - Zhiyu Zhang; Zejuan Li; Xiaohui Wu; Chun-Feng Zhang; Tyler Calway; Tong-Chuan He; Wei Du; Jianjun Chen; Chong-Zhi Wang; Chun-Su Yuan (Elsevier, 2015)
Among important components of American ginseng, protopanaxadiol (PPD) showed more active anticancer potential than other triterpenoid saponins. In this study, we determined the in vivo effects of PPD in a mouse cancer model first. Then, using human colorectal cancer cell lines, we observed significant cancer cell growth inhibition by promoting G1 cell cycle redistribution and apoptosis. Subsequently, we characterized the downstream genes targeted by PPD in HCT-116 cancer cells. Using Affymetrix high density GeneChips, we obtained the gene expression profile of the cells. Microarray data indicated that the expression levels of 76 genes were changed over two-fold after PPD, of which 52 were upregulated while the remaining 24 were downregulated. Ingenuity pathway analysis of top functions affected was carried out. Data suggested that by regulating the interactions between p53 and DR4/DR5, the tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) pathway played a key role in the action of PPD, a promising colon cancer inhibitory compound.